The organisation and evolution of a repeated DNA sequence family in related Allium species - Evans, Ian Jeffrey (1983)
A large proportion of the genomes of species belonging to the genus Allium comprises repetitive sequence DNA, a component implicated as a cause of the large variation in C-values between even closely related species. The work presented here represents part of the first phase in the characterisation of some of these repetitive sequences in a number of Allium species. One repetitive DNA sequence family, BIOOO, isolated from the genome of A. sativum, has been characterised with respect to the genomic organisation, reiteration frequency and sequence divergence of its members within A. sativum. Sequences sharing homology with a cloned representative member of the B1OOO family have been detected in the genomes of a number of other Allium species; such sequences display quantitative and qualitative modulations in their organisation. In addition, and by contrast, the distribution and organisation of a satellite DNA family present In a number of Allium species has been investigated; the characteristics of this family differ from those of the B1OOO family in many respects. Data relating to the evolution and maintenance, functions and effects of repetitive-sequence DNA in eukaryotic genomes are reviewed and where possible the data pertaining to Allium are discussed in context with such information from other species.